Transforming Education Fund Management: Leveraging Blockchain for Transparency, Fraud Reduction, and Efficiency - Marenta Claudia (Indonesia Auditing Research Journal, 2023)
This research explores the potential of blockchain technology in revolutionizing education fund management by enhancing transparency, reducing fraud, and improving the efficiency of fund allocation processes. Through a mixed-methods approach, including qualitative interviews, focus group discussions, surveys, and document analysis, insights were gathered from diverse stakeholders in the education finance ecosystem. The findings highlight the transformative impact of blockchain in increasing transparency through its decentralized and immutable ledger, enabling real-time tracking of fund flows and enhancing trust among stakeholders. Moreover, blockchain's cryptographic security features and smart contracts automate fund disbursement, reducing the risk of fraud and ensuring accountability in fund allocation processes. Furthermore, blockchain improves the efficiency of fund allocation by streamlining administrative processes, reducing bureaucratic overhead, and enabling direct peer-to-peer transactions. However, challenges such as technical complexities, regulatory uncertainties, and socio-economic factors must be addressed to realize the full potential of blockchain in education fund management.